Microeconomic foundation for Phillips curve with a three-period overlapping generations model and negative real balance effect - Yasuhito Tanaka (Central European Economic Journal (CEEJ), 2021)
We show a negative relation between the inflation rate and the unemployment rate, that is, the Phillips curve using a three-period overlapping generations (OLG) model with childhood period and pay-as-you-go pension for older generation under monopolistic competition with negative real balance effect. In a three-period OLG model, there may exist a negative real balance effect because consumers have debts and savings. A fall (or rise) in the nominal wage rate induces a fall (or rise) in the price, then by negative real balance effect, the unemployment rate rises (or falls), and we get a negative relation between the inflation rate and the unemployment rate. This conclusion is based on the premise of utility maximisation of consumers and profit maximisation of firms. Therefore, we present a microeconomic foundation for the Phillips curve. We also examine the effects of fiscal policy financed by seigniorage, which is represented by left-ward shift of the Phillips curve.
Keywords: E12; E24; E31; 330; microeconomic foundation; monopolistic competition; negative real balance effect; Phillips curve; a three-period overlapping generations model